Radio frequency fingerprints vs. physical unclonable functions - are they twins, competitors, or allies? - Zhang, Junqing (2024)
Privacy breaches and online frauds are grave concerns in pervasive computing. Device identification is the first line of defense to detect and stop fraud. Conventional device authentication schemes using software addresses as identities or static pre-programmed secret keys are vulnerable to tampering and memory attacks. This article reviews two emerging lightweight hardware-oriented solutions to avoid these problems, namely radio frequency fingerprint (RFF) identification and physical unclonable function (PUF) authentication. Their operating principles and protocols are first introduced, followed by a scrutiny of their common and distinctive features, and a discussion of the stumbling blocks in the way of their market adoption. Finally, we envisage a combined mutual authentication and key establishment scheme to shed light on their synergy.